TINJAUAN PELAKSANAAN PEKERJAAN PIER HEAD ABUTMENT 1 PADA PROYEK FLY OVER GELUMBANG - Adriansyah Lubis, Rizki; Rosyad, Farlin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Roads are transportation infrastructure capable of providing supporting services in the fields of education, trade, work, etc. As is the case with the Gelumbang railway track, it has a high level of congestion. So there is a need for good traffic management so that it can reduce the risk of accidents that occur while driving. A flyover is a model of a bridge that crosses over a road, whether toll roads, highways or flyovers, is an important means that supports human life and its activities are also a benchmark in the development of a region or even a country. According to Law Number 38 of 2004, roads as part of transportation infrastructure have an important role in the economic, socio-cultural, environmental, political, defense and security fields, and are used for the greatest prosperity of the people. One of the upper structures on a flyover is a pier head which functions as a foundation for the abutment head between the abutments or abutments and to distribute the working load to the abutments and bridge pillars.Keywords: Implementation of pier head work.